The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.01044
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq Profiling Showed Divergent Carbohydrate-Active Enzymes (CAZymes) Expression Patterns in Lentinula edodes at Brown Film Formation Stage Under Blue Light Induction

Abstract: Lentinula edodes (shiitake mushroom) is one of the most important edible mushrooms worldwide. The L. edodes cultivation cycle includes a unique developing stage called brown film formation that directly affects the development of primordium and the quality of fruiting body. Brown film formation is induced by light, especially blue light. To promote our understanding of the role of blue light in brown film formation mechanisms of L. edodes, we used RNA-seq and compared the transcriptomes of L. edodes grown unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 56 publications
(62 reference statements)
0
21
0
Order By: Relevance
“…Transcriptome analysis of different developmental stages of peridioles identified transcription factors (TFs) that may play a role in this regulation [ 16 ]. Previous studies on comparative transcriptome analysis have identified candidate genes involved in mycelium browning [ 17 , 18 ] and revealed a high rate of divergence in developmental gene expression as well as several genes with conserved expression patterns [ 19 , 20 ]. These studies indicate that RNA-seq provides an effective way to explore the underlying regulatory networks of favorable traits in fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis of different developmental stages of peridioles identified transcription factors (TFs) that may play a role in this regulation [ 16 ]. Previous studies on comparative transcriptome analysis have identified candidate genes involved in mycelium browning [ 17 , 18 ] and revealed a high rate of divergence in developmental gene expression as well as several genes with conserved expression patterns [ 19 , 20 ]. These studies indicate that RNA-seq provides an effective way to explore the underlying regulatory networks of favorable traits in fungi.…”
Section: Introductionmentioning
confidence: 99%
“…At present, several studies on the use of omics to study CAZymes have been published. For example, Huang et al ., 15 in their study used RNA‐seq to identify 52 upregulated CAZymes in Lentinula edodes , and found that these upregulated CAZymes may play important roles in brown film formation to provide sufficient nutrition for L. edodes . With metabolic and proteomic analysis, 139 CAZymes and 10 browning‐related enzymes were found to be involved in the texture and color regulation of morel fruiting bodies 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In the bacterial polysaccharide synthesis pathway, sugar nucleotides are the most basic glycosyl donor unit, and their efficient supply is the key to achieving the mass synthesis of polysaccharides [ 27 , 28 ]. Monosaccharides, mostly glucose in this study, need to undergo a series of reactions after they enter the cell to be converted into the glycosyl donor unit [ 29 ].…”
Section: Resultsmentioning
confidence: 99%